What drives U.S. current account fluctuations? - Alina Barnett; Roland Straub (European Central Bank (ECB), 2008)
We use a structural VAR with sign restrictions to jointly identify the impact of monetary policy, private absorption, technology and oil price shocks on current account fluctuations in the U.S.. We derive the sign restrictions from theoretical impulse response functions of a DSGE model with oil, ensuring that these are consistent with a broad range of parameter values. We find that a contractionary oil price shock has a negative effect on the current account which lasts for approximately 3 years. We also find that monetary policy shocks and private absorption shocks are the main drivers of historical current account deteriorations in the U.S. Furthermore, monetary policy shocks can explain approximately 60 percent at a one year forecast horizon, although this reduces to around 40 per cent at a 7 year horizon, whilst the oil price explains just under 10 percent of the forecast error variance of the U.S. current account.
Keywords: E0; F32; F4; 330; current account; global imbalances; sign restrictions; Leistungsbilanz; Gesamtwirtschaftliches Angebot; Geldpolitik; Schock; Ölpreis; USA